Respuesta productiva de conejos alimentados con follaje fresco de nacedero (Trichanthera gigantea, Lamiales:Acanthaceae) (UNED Research Journal, 2014)
Productive response of rabbits fed with fresh leaves of nacedero (Trichanthera gigantea, Lamiales:Acanthaceae). Rabbit production is a viable activity in Costa Rica. It offers consumers a high quality meat, and for farmers a good income with a relatively low investment. Production performance, including weight gain and dressing percentage of rabbits fed with two levels of fresh “nacedero” leaves (Trichanthera gigantea) were evaluated. The experiment was conducted in a commercial farm, using 30 weanling animals (California breed) randomly distributed among three treatments (ten animals per treatment): T1: Control: 100% commercial extruded diet, T2: 85:15, 85% commercial extruded diet and 15% nacedero fresh leaves, T3: 70:30, 70% commercial extruded diet and 30% nacedero fresh leaves. Animals were individually weighed weekly for eight weeks, then slaughtered at 88 days of age and dressing percentage calculated. Significant differences (p
Keywords: rabbit meat; food intake; nutrition; weight gain; Orytolagus cuniculus; Trichanthera gigantea.